THE INFLUENCE OF DER AND EPS ON STOCK RETURN OF FOOD AND BEVERAGE COMPANIES IN THE IDX DURING 2015–2019 PERIOD - Amelia Tanto (Accounting Study Program, Universitas Ciputra Surabaya, 2023)
This study aims to determine the effect of DER and EPS on stock returns of food and beverage companies on the Indonesia Stock Exchange during 2015–2019. The type of data in this study is secondary data. The samples in this study are 11 companies selected through purposive sampling. The total number of data in this study is 55, collected from 11 companies for 5 years. The data analysis methods used are descriptive statistical analysis, classical assumption test, and multiple regression analysis. The data processing software used is SPSS version 22 software. The results of this study indicate that DER and EPS have simultaneous effect on stock returns. From the t-test it was found that DER has a negative effect on stock returns and EPS has a positive effect on stock returns. DER affects stock returns negatively, namely when there is an increase in DER, stock returns will decrease. In addition, it is known that EPS positively affects stock returns, so that if there is an increase in EPS, then stock returns will also increase.